Pengaruh Penggunaan Teknologi dan Penerapan e-Procurement terhadap Kinerja Procurement - Viany Utami Tjhin (ULTIMA InfoSys, 2016)
This research aimed to determine the impact of the use of e-procurement technology and the use of e-procurement technology on the procurement performance at PT. VivaStor Techno Logica. The method used in this research consisted of three phases. The first stage is the study of literature that aims to deepen the knowledge about the topic of e-procurement and electronic procurement system (SPSE) on the Electronic Procurement Service (LPSE Ministry of Finance). The second stage was distributing questionnaires, which aims to obtain primary data from companies. The last step was observe the e-procurement business processes that are running on the website LPSE. The samples in this study using purposive sampling technique (judgment sampling). Questionnaires were distributed to users of e-procurement PT. VivaStor Techno Logica, then distributed questionnaires to 30 respondents. The results showed that the usage of e-procurement technology gives effect to the procurement practice at VivaStor Techno Logica; e-procurement technology usage has influences on procurement performance at PT. VivaStor Techno Logica; and procurement practices gives effect to procurement performance at PT. VivaStor Techno Logica. Index Terms – procurement practice, e-procurement technology usage, procurement performance